Effect of Supplementation of Aloe Vera Juice on the Carcass Traits of Japanese Quails - P, Jogeswar; P, Ponnuvel; D, Sreekumar; P K, Mandal; R, Ganesan; N, Elanchezhian (Journal of Meat Science, 2023)
An experiment was carried out using 300 Namakkal strain of Japanese quails from day old to five weeks of age to study the effect of aloe vera juice supplementation at different concentrations through drinking water on growth performance. The birds were divided into four treatment groups with three replicates in each treatment and each replicate had 25 birds. The four treatment groups consisted of control group without supplementation of aloe vera juice (T0), treatment group 1 (T1) with supplementation of aloe vera juice at the rate of 1 per cent, treatment group 2 (T2) with 1.5 per cent, and treatment group 3 (T3) with 2 per cent supplementation. Standard management and feeding practices were followed on all treatment groups. The carcass traits such as dressing, eviscerated and inedible parts percentage were recorded by randomly selecting two males and two females (four quails) per replicate i.e. six males and six females (12 quails) from each treatment group and executing a slaughter study at 35 days of age. The results revealed a significantly better (P<0.05) carcass traits such as dressing, eviscerated and inedible parts percentage, between all aloe vera juice supplemented groups and the control group and the best carcass yield was observed in T2 group.